2011
DOI: 10.1165/rcmb.2011-0031oc
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Phenotypic Differences of Asthmatic Epithelium and Its Inflammatory Responses to Respiratory Syncytial Virus and Air Pollution

Abstract: A substantial proportion of healthcare cost associated with asthma is attributable to exacerbations of the disease. Within the airway, the epithelium forms the mucosal immune barrier, the first structural cell defense against common environmental insults such as respiratory syncytial virus (RSV) and particulate matter. We sought to characterize the phenotype of differentiated asthmatic-derived airway epithelial cultures and their intrinsic inflammatory responses to environmental challenges. Air-liquid interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
169
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(193 citation statements)
references
References 76 publications
14
169
1
2
Order By: Relevance
“…Both the asthmatic grafted epithelium and the asthmatic human lung biopsy tissue show decreased E-cadherin expression. This is all consistent with our previous work showing that, when differentiated at air-liquid interface culture, asthmatic-derived epithelial cells are less differentiated in comparison to nonasthmatic-derived cells, as demonstrated by increased basal cell number and lack of E-cadherin (5,6,11,19).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Both the asthmatic grafted epithelium and the asthmatic human lung biopsy tissue show decreased E-cadherin expression. This is all consistent with our previous work showing that, when differentiated at air-liquid interface culture, asthmatic-derived epithelial cells are less differentiated in comparison to nonasthmatic-derived cells, as demonstrated by increased basal cell number and lack of E-cadherin (5,6,11,19).…”
Section: Discussionsupporting
confidence: 93%
“…An important feature of asthma is the loss of junction proteins in the airway epithelium (18), such as E-cadherin (19). This is demonstrated in asthmatic human airway tissue by a 35% lower level of E-cadherin compared with nonasthmatic tissues ( Figure 2C).…”
Section: Establishment Of the Asthmatic Airway Epithelial Xenograft Smentioning
confidence: 92%
“…Such changes have been seen to correspond to an increase in ionic and macromolecular permeability (Xiao et al, 2011;Bai et al, 2015;Freishtat et al, 2011;Watson et al, 2010). It has also been shown that the permeability of the bronchial epithelial cell layer is only increased in asthmatic subjects after exposure to ozone or nitrogen dioxide (Bayram et al, 2002), and that mediator release is altered after exposure of ALI cultures from asthmatic donors to respiratory syncytial virus (RSV) or particulate matter (Hackett et al, 2011b). Using cells derived from patients with COPD, ALI cultures show higher baseline levels of cytokine expression and increased susceptibility to RSV infection, despite an increased IFN response tem is specially designed for direct contact between cells and components of the test atmosphere at the air/liquid interface.…”
Section: Fully Differentiated 3d Human Airway Epithelial Modelsmentioning
confidence: 99%
“…Epithelial cell-to-cell contacts, however, may become compromised in the airways of subjects with asthma, allowing epithelial cell mediators to reach the underlying structural cells. Several studies show that many adhesion proteins necessary for epithelial cell-to-cell contacts are downregulated in the airway epithelium of patients with asthma (131)(132)(133). Because of this uncertainty, determining the circumstances under which airway epithelium and subepithelium modify HASM contraction and relaxation responses will be essential for future studies investigating the effect of the surrounding milieu on HASM contraction and AHR.…”
Section: Contraction Cell Shortening and Cytoskeletal Motorsmentioning
confidence: 99%